Naturally occurring and synthetic β‐carbolines as cholinesterase inhibitors - Ghosal S.; Mehta R.; Bhattacharya S.K. (My University, 2025)
Inhibitory activities of a number of naturally occurring and synthetic aromatic and tetrahydro‐β‐carbolines toward true and pseudocholinesterases were investigated. The potencies of the active compounds were measured and compared with those of physostigmine by their ability to protect acetylcholine from the cholinesterase (assayed on frog rectus abdominis muscle) and by using the chromodacryorrhea test in albino rats. Some quaternary aromatic β‐carbolines were found to be about one‐sixth as potent as physostigmine. The inhibitory potencies were nearly the same against acetylcholinesterase and pseudocholinesterase. The tertiary aromatic β‐carbolines showed only weak activity, while the tetrahydro‐β‐carbolines lacked this activity. Influence of indole‐N‐methylation on the inhibitory activity was greater with the quaternary β‐carbolines than with the tertiary series. The activity also depended on the degree of extended conjugation of the inhibitor molecule. Other factors involved in the anticholinesterase activities of the β‐carbolines were examined, and a plausible mechanism of action was proposed. Copyright © 1972 Wiley‐Liss, Inc., A Wiley Company